2021
DOI: 10.1007/s10901-021-09852-x
|View full text |Cite
|
Sign up to set email alerts
|

Intervening in the cycle of poverty, poor housing and poor health: the role of housing providers in enhancing tenants’ mental wellbeing

Abstract: Poverty, poor housing and poor health are complexly interconnected in a cycle that has proven resistant to intervention by housing providers or policy makers. Research often focuses on the impacts of the physical housing defects, particularly upon rates of (physical) illness and disease. There has been comparatively little research into the ways in which housing services can underpin the generation of positive health and, especially, wellbeing. Drawing on qualitative data from 75 tenants in the social and priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…It is rather consensual that housing and employment are pivotal structures for the satisfaction of fundamental psychological needs, and subjective and psychological wellbeing. As Garnham et al (2021) highlight, poverty, poor housing, and poor health (mental and physical health), are heavily interwoven. Growing scientific literature places insecure employment as associated with poorer mental health (Bentley et al, 2019).…”
Section: Double Precarity and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…It is rather consensual that housing and employment are pivotal structures for the satisfaction of fundamental psychological needs, and subjective and psychological wellbeing. As Garnham et al (2021) highlight, poverty, poor housing, and poor health (mental and physical health), are heavily interwoven. Growing scientific literature places insecure employment as associated with poorer mental health (Bentley et al, 2019).…”
Section: Double Precarity and Healthmentioning
confidence: 99%
“…Housing stability is a highly relevant determinant of positive well-being. It has been found that tenants' financial stability and resilience to overcome unstable economic-real-estate markets undermine individuals' sense of home (Garnham et al, 2021). This is understandable because this sense of home depends, and is implied on individuals' identity formation, sense of privacy, comfort, and stability (Garnham et al, 2021).…”
Section: Double Precarity and The Sense Of Selfmentioning
confidence: 99%
“…‘Place’ is important because those living in very low income areas can feel poorly served by local services, regardless of the tenure of their housing, this can then lead to a feelings of abandonment and isolation from other people living in the neighbourhood and, hence, poor health and wellbeing [ 9 ]. Consequently, there have been questions about the extent to which the private and social rental sectors should provide homes, not just houses [ 32 , 33 ]. Garnham et al [ 32 ] (p. 1) found that, in Glasgow, for renters, a home was a ‘recuperative space in which to shelter from daily stressors and was a source of autonomy and social status’, which was underpinned by the ‘housing service, property quality and affordability’.…”
Section: Summary Of Current Researchmentioning
confidence: 99%
“…Consequently, there have been questions about the extent to which the private and social rental sectors should provide homes, not just houses [ 32 , 33 ]. Garnham et al [ 32 ] (p. 1) found that, in Glasgow, for renters, a home was a ‘recuperative space in which to shelter from daily stressors and was a source of autonomy and social status’, which was underpinned by the ‘housing service, property quality and affordability’. Consequently, living in a safe, well maintained, and affordable home, as well as social connections with others in the community and employment, are key contributors to mental wellbeing.…”
Section: Summary Of Current Researchmentioning
confidence: 99%
“…This paper thus aims to investigate a) whether private renters in shared living arrangements had better or worse mental well-being outcomes during the COVID-19 pandemic compared with other household types, and b) to what extent housing conditions contributed to mental well-being outcomes in shared living arrangements. Poor rental housing conditions undermine tenants’ feelings of home, which in turn, have negative effects on mental well-being (Garnham et al, 2022 ). Given the increased time at home and mental health impacts of the pandemic, it is important to study how the impact of housing conditions may be exacerbated by this major event.…”
Section: Introductionmentioning
confidence: 99%